دور إدارة الموارد البشرية في تنفيد إستراتيجية المؤسسة تجاه المسؤولية الاجتماعية -دراسة حالة الجزائرية القطرية للصلب- : The role of HRM in implementing company’s strategy towards corporate social responsibility - Case study of Algerian Qatari Steel (AQS) - - كريد فيصل, (Journal of North African Economies, 2025)
This study aims to conceive a strategic fit model through which we can identify and analyze company’s strategic behaviors towards Corporate Social Responsibility (CSR), and depict the role of HRM in achieving those behaviors, by gathering them into three levels, at each one HRM contributes with a kit of practices. We used the proposed model to evaluate the engagement of Alegerian Qatari steel (AQS) in social and environmental dimensions, and determine the nature of the corresponding fit. We concluded that the group adopts three strategies: (1) irresponsible strategy (secondary) with irresponsible fit, (2) implicit strategy (away from the core of business) with legal fit, and (3) two explicit strategies (temporary and principal) with proactive fit. In th end, we advanced some recommendations hoping that improve the status quo of the studied company; as mitigating the severity of the irresponsible strategy (lobbying to reduce apprenticeship’s cots), diversifying talents’ sources, and adopting the KPIs issued by the World Steel Association (WSA).